Design and development of smart whiteboard cleaner in classroom application - Suzilawati Binti Alias (Southeast Asian Journal of Technology and Science, 2020)
Nowadays, whiteboards are used widely in higher educational centre over the world. The whiteboards usually are cleaned manually using manpower. This study offers a solution to clean the whiteboard automatically called Smart Whiteboard Cleaner. The idea gained after viewing the manual process of whiteboard cleaning in polytechnics in ways to provide some comfort for teachers while cleaning the whiteboard. Smart Whiteboard Cleaner is a tool which can move up and down to clean the whiteboards by pressing the button called Double Pole Double Throw (DPDT) button and powered with the help of DC Motor 12V. Smart Whiteboard Cleaner will be implement to facilitate the process of the classroom housekeeping. The result is compared between manual duster cleaning and Smart Whiteboard Cleaner. Finding shows that manual duster cleaning completed after 6.53 seconds while Smart Whiteboard Cleaner only takes 4.01 seconds. This makes Smart Whiteboard Cleaner worth to use as it can save time. In conclusion, Smart Whiteboard Cleaner is a good option used to facilitate the process of the whiteboard cleaning as it can be cleaned in an easy and can provide convenient ways of use.